Modified lfo lithium supplement material, preparation method thereof, positive plate and lithium ion battery

CN123018187APending Publication Date: 2026-10-30SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611405466.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

解决了现有技术中存在的LFO加工性能差以及高温存储循环产气的问题

Benefits of technology

(1)本发明提供的改性LFO补锂剂材料,其残碱量低,这有利于抑制制浆过程中与粘结剂的副反应,确保补锂浆料粘度稳定,表现出优异的加工性能;且该材料经过高价态离子掺杂后,晶格更加稳定,脱锂后副产物不会出现破碎,避免了新界面产生,可以有效抑制高温存储循环产气。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of lithium ion batteries, in particular to a modified LFO lithium supplementing agent material, a preparation method thereof, a positive plate and a lithium ion battery. 1‑x M x The general formula of the lithium supplementing agent matrix is Li5Fe 1‑x M x O4, M is a high-valence doped ion, the valence of the high-valence doped ion is +4, +5 or +6; and 0.001≤x≤0.02; the residual alkali content in the modified LFO lithium supplementing agent material is ≤1000ppm. The residual alkali content in the material is low, which is conducive to inhibiting the side reaction with the binder during the pulping process, ensuring the viscosity stability of the lithium supplementing slurry, thereby improving the processing performance; and after the material is doped with the high-valence ion, the crystal lattice is more stable, the by-product after delithiation will not be broken, and the generation of a new interface is avoided, which can effectively inhibit the gas production during high-temperature storage cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a modified LFO lithium replenishing agent material and its preparation method, a positive electrode sheet, and a lithium-ion battery. Background Technology

[0002] Lithium-ion batteries have become a promising secondary battery for energy storage due to their advantages such as high discharge voltage, high specific energy density, long cycle life, and wide applicable temperature range.

[0003] Both lithium iron phosphate batteries and ternary lithium batteries have a need to improve energy density and cycle life, and pre-lithiation technology is an effective way to address this need. Among them, cathode pre-lithiation is the most widely used and safest pre-lithiation technology.

[0004] Currently, the main lithium replenishing agents used in cathodes include lithium iron ferrite and lithium nickel ferrite. Among them, lithium iron ferrite Li5FeO4 (LFO) has higher lithium replenishment efficiency and is more cost-effective. However, lithium iron ferrite also has some problems: First, it is difficult to process. During the homogenization process, the high residual alkali content of the material leads to rapid viscosity rebound of the slurry and easy formation of gel. Second, it has the problem of continuous gas generation during high-temperature cycling or high-temperature storage.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] The primary objective of this invention is to provide a modified LFO lithium supplement material with low residual alkali content. This low content helps suppress side reactions with the binder during slurry preparation, ensuring stable viscosity of the lithium supplement slurry and thus improving processing performance. Furthermore, the material, after being doped with high-valence ions, exhibits a more stable crystal lattice, preventing breakage of byproducts after delithiation and avoiding the formation of new interfaces. This effectively suppresses gas generation during high-temperature storage cycles. This addresses the problems of poor LFO processing performance and gas generation during high-temperature storage cycles in existing technologies.

[0007] The second objective of this invention is to provide a method for preparing a modified LFO lithium supplement material. This method involves preparing crystalline materials via microwave heating, precisely and efficiently using microwave energy for crystal synthesis. This improves the conversion rate of the crystalline materials, thereby reducing the amount of residual alkali generated. Consequently, the modified LFO lithium supplement material has a low residual alkali content, effectively suppressing side reactions with the binder during slurry preparation, ensuring stable viscosity of the lithium supplement slurry, and improving processing performance. Furthermore, after high-valence ion doping, the crystal lattice becomes more stable, preventing byproduct breakage after delithiation and avoiding the formation of new interfaces, thus effectively suppressing gas generation during high-temperature storage cycles.

[0008] A third objective of this invention is to provide a positive electrode.

[0009] The fourth objective of this invention is to provide a lithium-ion battery with high capacity and low gas production during high-temperature storage and cycling.

[0010] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: This invention first provides a modified LFO lithium replenishing agent material, comprising a lithium replenishing agent matrix and a carbon coating layer covering the lithium replenishing agent matrix; the general formula of the lithium replenishing agent matrix is ​​Li5Fe. 1-x M x O4; wherein M is a high-valence dopant ion, and the valence of the high-valence dopant ion is +4, +5 or +6; and 0.001≤x≤0.02; the residual alkali content in the modified LFO lithium replenishing agent material is ≤1000ppm.

[0011] Furthermore, the high-valence doped ions include V 5+ 、Nb 5+ Mo 6+ Ti 4+ Ce 4+ and Pr 4+ One or more of them.

[0012] Furthermore, 0.01 < x ≤ 0.02.

[0013] Furthermore, the thickness of the carbon coating layer is 2nm~10nm.

[0014] Furthermore, the carbon content in the modified LFO lithium supplement material is 1 wt.% to 3 wt.%.

[0015] Furthermore, the particle size D50 of the modified LFO lithium supplement material is 2μm~12μm.

[0016] This invention also provides a method for preparing a modified LFO lithium supplement material, comprising the following steps: mixing a lithium source, an iron source, an M source, and a solvent to prepare a precursor material; intermittently microwave heating the precursor material to allow high-valence doped ions M from the M source to enter the LFO lattice, thereby obtaining a crystalline material; mixing the crystalline material with a carbon source solution and drying it, followed by microwave treatment to form a carbon coating layer, thereby obtaining the modified LFO lithium supplement material.

[0017] Furthermore, the intermittent microwave heating includes a heating phase and a resting phase that are alternately performed in cycles, the number of cycles being 2 to 6, the duration of each heating phase being 2.5 min to 5 min, the duration of each resting phase being 2.5 min to 5 min, the total duration of each heating phase being 5 min to 30 min, and the power being 400 W to 800 W.

[0018] Furthermore, the container holding the precursor material for intermittent microwave heating is a quartz container or a corundum container.

[0019] Furthermore, the method for preparing the precursor material by mixing lithium source, iron source, M source and solvent specifically includes: mixing lithium source, iron source, M source, solvent and complexing agent, heating and evaporating and drying to obtain a dry gel; heating and pre-decomposing the dry gel to obtain the precursor material.

[0020] Furthermore, the heating and evaporation is carried out by water bath heating, the heating and evaporation temperature is 70℃~90℃, and the heating and evaporation time is 5h~10h.

[0021] Furthermore, the solvent includes water.

[0022] Furthermore, the complexing agent includes at least one of citric acid and EDTA.

[0023] Furthermore, the molar amount of the complexing agent is 1.2 to 2.0 times the molar amount of Fe in the iron source.

[0024] Furthermore, the temperature for the pre-decomposition heating is 300℃~350℃, the pre-decomposition heating time is 2h~4h, and the pre-decomposition heating atmosphere is an inert atmosphere.

[0025] Furthermore, the carbon source in the carbon source solution includes at least one of sucrose, glucose, and polyethylene glycol.

[0026] Furthermore, in the process of drying the crystal material after mixing it with the carbon source solution, the drying temperature is 80℃~100℃.

[0027] Furthermore, the microwave treatment method for forming the carbon coating layer is an intermittent low-temperature microwave treatment, specifically including alternating heating treatment and resting treatment, the number of cycles being 2 to 4, the time of each heating treatment being 2.5 min to 5 min, the time of each resting treatment being 2.5 min to 5 min, the total time of all heating treatments being 5 min to 20 min, and the power being 200W to 400W.

[0028] The present invention further provides a positive electrode sheet, which includes a positive current collector and a positive electrode material layer disposed on the surface of the positive current collector; the positive electrode material layer contains the above-mentioned modified LFO lithium supplement material or the modified LFO lithium supplement material prepared according to the above-mentioned method for preparing modified LFO lithium supplement material.

[0029] The present invention also provides a lithium-ion battery comprising the above-described positive electrode.

[0030] Furthermore, the lithium-ion battery has a 0.5C charging capacity of ≥750mAh / g.

[0031] Furthermore, the lithium-ion battery, at 45°C and 2.0~3.65V, produces ≤0.5mL / Ah gas per 1000 cycles at 1C / 1C.

[0032] Furthermore, the lithium-ion battery produces ≤0.6 mL / Ah when stored at 55°C for 60 days.

[0033] Furthermore, the lithium-ion battery maintains a capacity retention rate of ≥97% after 1000 cycles at 45°C and 2.0~3.65V using 1C / 1C. Compared with the prior art, the beneficial effects of the present invention are: (1) The modified LFO lithium supplement material provided by the present invention has a low residual alkali content, which is beneficial to suppress the side reaction with the binder during the slurry preparation process, ensure the viscosity of the lithium supplement slurry is stable, and exhibit excellent processing performance; and after the material is doped with high valence ions, the lattice is more stable, and the by-products after delithiation will not break, avoiding the generation of new interfaces, which can effectively suppress the gas generation during high-temperature storage cycle.

[0034] (2) The modified LFO lithium supplement material provided by the present invention has a widened lithium ion channel after being doped with high valence ions, which improves the lithium ion diffusion rate and thus improves the specific capacity of the material; at the same time, the carbon coating layer makes the material have a perfect conductive network, which can improve the conductivity of the material and further improve the specific capacity of the material.

[0035] (3) The method for preparing modified LFO lithium supplement material provided by the present invention prepares crystal material by microwave heating. The microwave energy is used precisely and efficiently for the synthesis of crystal material, which can improve the conversion rate of crystal material and reduce the amount of residual alkali generated. Therefore, the residual alkali in the modified LFO lithium supplement material is low, which effectively inhibits the side reaction with binder during the slurry preparation process, ensures the viscosity of the lithium supplement slurry is stable, and improves the processing performance. After high-valence ion doping, the lattice is more stable, and the by-products after delithiation will not break, avoiding the generation of new interfaces, thereby effectively inhibiting the gas generation during high-temperature storage cycle. At the same time, after high-valence ion efficient doping, the lithium ion channel is widened, thereby improving the lithium ion diffusion rate and thus improving the specific capacity of the material.

[0036] (4) The method for preparing the modified LFO lithium supplement material provided by the present invention forms a carbon coating layer by microwave treatment. The microwave energy is used precisely and efficiently for the formation reaction of the carbon coating layer. The graphitization degree is high, and the resulting carbon coating layer is uniform and complete, forming a complete conductive network, thereby significantly improving the conductivity of the modified LFO lithium supplement material.

[0037] (5) The method for preparing modified LFO lithium replenishing agent material provided by the present invention uses microwave heating to achieve efficient doping of high-valence ions in the material, which makes the crystal structure of the material more stable and the carbon coating layer more complete and dense. The two work together to make the byproducts after LFO detachment in an inert state, so that no side reaction will be generated to consume active lithium, thereby reducing capacity loss during cycling and effectively improving cycle life. It also prevents the electrolyte from oxidizing under high temperature cycling and storage conditions, thus effectively reducing the amount of gas produced.

[0038] (6) The preparation method of the modified LFO lithium supplement material provided by the present invention is simple, easy to implement and highly efficient. Through the coordination of each step, the modified LFO lithium supplement material obtained has excellent electrochemical performance and processing performance. Detailed Implementation

[0039] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0040] Unless otherwise specified, in this invention, terms such as "first aspect," "second aspect," "third aspect," and "fourth aspect" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, terms such as "first," "second," "third," and "fourth" serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.

[0041] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0042] Unless otherwise specified, in this invention, "one or more" or "at least one" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.

[0043] In a first aspect, the present invention provides a modified LFO lithium replenishing agent material, which is a modified lithium iron ferrite rich in lithium, specifically comprising a lithium replenishing agent matrix and a carbon coating layer covering the outer surface of the lithium replenishing agent matrix.

[0044] The general formula of the lithium supplement matrix is ​​Li5Fe 1-x M x O4; where M is a high-valence dopant ion with a valence of +4, +5, or +6; and 0.001 ≤ x ≤ 0.02. x can be, for example, 0.001, 0.003, 0.005, 0.008, 0.01, 0.015, 0.02, etc. That is, the doping amount of the high-valence dopant ion is 1000 ppm to 20000 ppm, for example, 1000 ppm, 5000 ppm, 8000 ppm, 10000 ppm, 15000 ppm, 20000 ppm, etc., where ppm refers to mole fraction.

[0045] The modified LFO lithium supplement material has a residual alkali content ≤1000ppm, where ppm is a mass fraction and residual alkali content refers to the total content of lithium hydroxide and lithium carbonate. A low residual alkali content helps suppress side reactions with the binder during the slurry preparation process, ensuring stable viscosity of the lithium supplement slurry and thus exhibiting excellent processing performance. Preferably, the residual alkali content in the modified LFO lithium supplement material is ≤600ppm. Preparing crystalline materials via microwave heating allows for precise and efficient use of microwave energy in the synthesis of crystalline materials, improving the conversion rate and reducing the amount of residual alkali generated; therefore, the modified LFO lithium supplement material has a low residual alkali content.

[0046] The modified LFO lithium supplement material provided by this invention is prepared by microwave heating. The microwave energy is used precisely and efficiently for the synthesis of the crystal material, which can improve the conversion rate of the crystal material and reduce the amount of residual alkali generated. Therefore, the residual alkali content in this modified LFO lithium supplement material is low, which can effectively suppress the side reaction with the binder during the slurry preparation process, ensure the viscosity of the lithium supplement slurry is stable, and thus improve the processing performance. At the same time, microwave heating can achieve efficient doping of high-valence ions, thereby making the crystal lattice more stable. The by-products after delithiation will not break, avoiding the generation of new interfaces and effectively suppressing gas generation during high-temperature storage cycles.

[0047] Furthermore, after the modified LFO lithium supplement material is efficiently doped with high-valence ions, the lithium-ion channels are widened, thereby increasing the lithium-ion diffusion rate and thus improving the specific capacity of the material. At the same time, microwave heating can obtain a uniform, complete and dense carbon coating layer, which gives the material a complete conductive network, thereby improving the material's conductivity and further increasing the specific capacity of the material.

[0048] In some specific embodiments, the high-valence doped ions include V 5+ 、Nb 5+ Mo 6+ Ti 4+ Ce 4+ and Pr 4+ One or more of them.

[0049] Preferably, 0.01 < x ≤ 0.02. x being within this range indicates a higher doping concentration of high-valence ions, which is beneficial for further improving the capacity of the modified LFO lithium replenisher material and suppressing gas generation during high-temperature storage cycles.

[0050] In some specific embodiments, the thickness of the carbon coating layer is 2nm to 10nm, for example, it can be 2nm, 5nm, 8nm, 10nm, etc. This is beneficial for forming a continuous, uniform and dense conductive network on the surface of the lithium supplement matrix, thereby improving the electronic conductivity of the modified LFO lithium supplement material and avoiding the obstruction of lithium ion transport due to excessive carbon layer thickness.

[0051] In some specific embodiments, the carbon content in the modified LFO lithium supplement material is 1 wt.% to 3 wt.%, for example, it can be 1 wt.%, 2 wt.%, 3 wt.%, etc. Controlling the carbon content within the range of 1 wt.% to 3 wt.% enables the formation of a moderately thick, continuous, and uniform carbon coating layer on the surface of the lithium supplement matrix. This effectively improves the electronic conductivity of the material while avoiding the obstruction of lithium-ion transport due to an excessively thick carbon layer.

[0052] In some specific embodiments, the particle size D50 of the modified LFO lithium supplement material is 2μm to 12μm, for example, it can be 2μm, 5μm, 8μm, 10μm, 12μm, etc. Controlling the particle size within this range can ensure sufficient contact between the material and the conductive agent and binder to build a highly efficient conductive network, while avoiding severe agglomeration and increased side reactions caused by excessively fine particles, thus achieving both high electronic conductivity and high initial coulombic efficiency.

[0053] In some specific embodiments, the modified LFO lithium supplement material is obtained by microwave heating to dope LFO with high-valence ions and then coating it with carbon. The efficient doping with high-valence ions broadens the lithium-ion transport channels, increases the lithium-ion diffusion rate, and thus improves the specific capacity of the material. Furthermore, the microwave heating method for carbon coating results in a high degree of graphitization, producing a uniform, complete, and dense carbon coating layer, thus creating a complete conductive network, which improves the material's conductivity and further enhances its capacity.

[0054] Meanwhile, microwave heating enables efficient doping of high-valence ions in the material, making the crystal structure of the material more stable and the carbon coating layer more complete and dense. This makes the byproducts after LFO detachment in an inert state, preventing side reactions that consume active lithium. Consequently, capacity loss during cycling is reduced, cycle life is longer, and the electrolyte will not be oxidized under high-temperature cycling and storage conditions, thus reducing the amount of gas produced.

[0055] Secondly, the present invention provides a method for preparing a modified LFO lithium supplement material, comprising the following steps: Precursor materials are prepared by mixing lithium source, iron source, M source and solvent.

[0056] The precursor material is then subjected to intermittent microwave heating, which causes the high-valence doped ions M in the M source to enter the LFO lattice. After cooling, the crystal material is obtained.

[0057] The crystalline material is then mixed evenly with a carbon source solution and dried, followed by microwave treatment to form a carbon coating layer, thus obtaining a modified LFO lithium supplement material.

[0058] The method for preparing modified LFO lithium supplement material provided by this invention prepares crystalline material by microwave heating. The microwave energy is used precisely and efficiently for the synthesis of crystalline material, which can improve the conversion rate of crystalline material and reduce the amount of residual alkali generated. Therefore, the residual alkali content in the modified LFO lithium supplement material is low, which effectively inhibits the side reaction with the binder during the slurry preparation process, ensures the stability of the viscosity of the lithium supplement slurry, and improves the processing performance.

[0059] Furthermore, microwave heating enables high-valence doped ions M to efficiently enter the LFO lattice, achieving efficient doping of high-valence ions and making the lattice more stable. Consequently, byproducts after delithiation will not break, avoiding the formation of new interfaces and effectively suppressing gas generation during high-temperature storage cycles. At the same time, after efficient doping of high-valence ions, the lithium-ion channels are widened, thereby increasing the lithium-ion diffusion rate and thus improving the specific capacity of the material.

[0060] Similarly, by forming a carbon coating layer through microwave treatment, microwave energy is used precisely and efficiently for the formation reaction of the carbon coating layer. The graphitization degree is high, and the resulting carbon coating layer is uniform and complete, forming a complete conductive network, thereby significantly improving the conductivity of the modified LFO lithium supplement material.

[0061] In addition, microwave heating enables efficient doping of high-valence ions in the material, making the crystal structure of the material more stable and the carbon coating layer more complete and dense. These two factors work together to make the byproducts after LFO removal in an inert state, so that no side reactions will occur that consume active lithium. This reduces capacity loss during cycling and effectively improves cycle life. It also prevents the electrolyte from oxidizing under high-temperature cycling and storage conditions, thus reducing the amount of gas produced.

[0062] The preparation method is simple, easy to implement, and highly efficient. Through the coordination of each step, the modified LFO lithium supplement material obtained has excellent electrochemical performance (high capacity, low gas production during high-temperature storage and cycling) and processing performance (stable viscosity of positive electrode lithium supplement slurry). Its performance is significantly better than that of LFO synthesized by traditional solid-state method.

[0063] In some specific embodiments, the intermittent microwave heating includes alternating heating and resting phases. The number of cycles is 2 to 6, for example, 2, 3, 4, 5, or 6. The duration of each heating phase is 2.5 to 5 minutes, for example, 2.5 minutes, 3 minutes, 4 minutes, and 5 minutes. The duration of each resting phase is also 2.5 to 5 minutes, for example, 2.5 minutes, 3 minutes, 4 minutes, and 5 minutes. The total duration of all heating phases is 5 to 30 minutes, for example, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes. The power is 400W to 800W, for example, 400W, 600W, and 800W. That is, after heating for a period of time, the sample is allowed to rest for a period of time before heating again, and this process is repeated. Intermittent microwave heating can prevent excessive crystal growth, improve molecular uniformity, and precisely control grain size. Using this high power and energy allows high-valence doped ions M from the M source to efficiently enter the LFO lattice. If the power is too low, it will reduce the doping efficiency of the high-valence doped ion M.

[0064] In some specific embodiments, the container holding the precursor material for intermittent microwave heating is a quartz container or a corundum container, which are relatively stable and less prone to introducing impurities.

[0065] In some specific embodiments, during the intermittent microwave heating of the precursor material, the microwave heating atmosphere is an inert atmosphere, such as high-purity argon or high-purity nitrogen.

[0066] In some specific embodiments, the method for preparing the precursor material by mixing lithium source, iron source, M source, and solvent specifically includes: First, using the sol-gel method, the lithium source, iron source, M source, solvent, and complexing agent are mixed evenly according to the stoichiometric ratio in the target molecular formula, then heated and evaporated, and dried to obtain a dry gel. The sol-gel method enables the reactants to achieve molecular and atomic-level mixing in the liquid phase, resulting in extremely uniform component distribution. The complexing agent inhibits the hydrolysis of iron ions, thus stabilizing the precursor and controlling the particle size of the final product. Then, the dry gel is pre-decomposed by heating to decompose the complexing agent, preventing the generation of large amounts of gas during subsequent heating, followed by cooling to obtain the precursor material.

[0067] In some specific embodiments, the heating and evaporation is water bath heating, and the heating and evaporation temperature is 70℃~90℃, for example, 70℃, 75℃, 80℃, 85℃, 90℃, etc.; the heating and evaporation time is 5h~10h, for example, 5h, 6h, 7h, 8h, 9h, 10h, etc.

[0068] In some specific embodiments, the solvent includes water.

[0069] In some specific embodiments, the complexing agent includes at least one of citric acid and EDTA.

[0070] In some specific embodiments, the molar amount of the complexing agent is 1.2 to 2.0 times the molar amount of Fe in the iron source, for example, it can be 1.2 times, 1.5 times, 1.8 times, 2.0 times, etc. Using this amount is beneficial for the hydrolysis of iron ions, leading to precipitation, i.e., stabilizing the precursor.

[0071] In some specific embodiments, the lithium source is a lithium-containing compound, preferably a soluble compound.

[0072] In some specific embodiments, the iron source is a compound containing lithium iron phosphate, preferably a soluble compound.

[0073] In some specific embodiments, the M source is a compound containing M.

[0074] In some specific embodiments, the pre-decomposition temperature is 300℃~350℃, for example, 300℃, 320℃, 350℃, etc. The pre-decomposition time is 2h~4h, for example, 2h, 3h, 4h, etc. The pre-decomposition atmosphere is an inert atmosphere, such as high-purity argon or nitrogen. Preferably, the pre-decomposition is carried out in a tube furnace.

[0075] In some specific embodiments, the carbon source in the carbon source solution includes at least one of sucrose, glucose, and polyethylene glycol.

[0076] In some specific embodiments, during the drying process after mixing the crystalline material with the carbon source solution, the drying temperature is 80℃~100℃, for example, 80℃, 90℃, 100℃, etc.; preferably, the drying is carried out until the moisture content in the material is less than 1000ppm, where ppm is a mass fraction. The drying is preferably oven drying.

[0077] In some specific embodiments, the microwave treatment method for forming the carbon coating layer is an intermittent low-temperature microwave treatment. Specifically, the intermittent low-temperature microwave treatment includes alternating heating and settling processes, with the number of cycles being 2 to 4 times, for example, 2, 3, or 4 times. The duration of each heating process is 2.5 to 5 minutes, for example, 2.5 minutes, 3 minutes, 4 minutes, and 5 minutes. The duration of each settling process is also 2.5 to 5 minutes, for example, 2.5 minutes, 3 minutes, 4 minutes, and 5 minutes. The total duration of all heating processes is 5 to 20 minutes, for example, 5 minutes, 10 minutes, 15 minutes, and 20 minutes. The power is 200W to 400W, for example, 200W, 300W, and 400W. This moderate power is beneficial for obtaining a complete and uniform carbon coating layer. If the power is too high, the carbon source will decompose rapidly, causing boiling and splashing, resulting in the inability to obtain a complete and uniform carbon coating layer. Furthermore, the intermittent low-temperature microwave treatment can also prevent the rapid decomposition of the carbon source, which would otherwise prevent the acquisition of a complete and uniform carbon coating layer.

[0078] In some specific embodiments, the atmosphere of the intermittent low-temperature microwave treatment is an inert atmosphere, such as high-purity argon or high-purity nitrogen.

[0079] Thirdly, the present invention provides a positive electrode sheet, comprising a positive current collector and a positive electrode material layer disposed on the surface of the positive current collector. The positive electrode material layer contains the aforementioned modified LFO lithium supplement material or a modified LFO lithium supplement material prepared according to the aforementioned method for preparing the modified LFO lithium supplement material.

[0080] In some specific embodiments, the positive electrode active material, modified LFO lithium supplement material, conductive agent, binder and solvent are mixed to form a slurry. Preferably, the viscosity of the slurry is 5500~7000 mPa·s. Then, the positive electrode slurry is coated on the positive electrode current collector and dried to obtain the positive electrode sheet.

[0081] Fourthly, the present invention provides a lithium-ion battery comprising the above-mentioned positive electrode sheet.

[0082] Optionally, the lithium-ion battery also includes a negative electrode, a separator, and an electrolyte, which are not limited in this invention.

[0083] This lithium-ion battery has high capacity, long cycle life, and low gas production during high-temperature storage cycles.

[0084] In some specific embodiments, the lithium-ion battery containing the modified LFO lithium replenishing agent material has a 0.5C charging specific capacity ≥ 750 mAh / g. The modified LFO lithium replenishing agent material provided by this invention, after efficient doping with high-valence ions, widens the lithium-ion channels, thereby improving the lithium-ion diffusion rate and the specific capacity of the battery made from this material; simultaneously, the carbon coating layer provides a complete conductive network, improving the material's conductivity and further enhancing the specific capacity of the battery made from this material.

[0085] In some specific embodiments, the lithium-ion battery containing the modified LFO lithium replenishing agent material exhibits a gas production rate of ≤0.5 mL / Ah after 1000 cycles at 45°C and 2.0~3.65V at 1C / 1C. The modified LFO lithium replenishing agent material provided by this invention has a low residual alkali content and a more stable lattice after high-valence ion doping. This prevents the breakage of byproducts after delithiation, avoiding the formation of new interfaces, and thus effectively suppresses gas production during high-temperature storage cycling of the battery made from it.

[0086] In some specific embodiments, the lithium-ion battery containing the modified LFO lithium replenisher material exhibits a capacity retention rate of ≥97% after 1000 cycles at 45°C and 2.0~3.65V using a 1C / 1C method. The modified LFO lithium replenisher material provided by this invention achieves efficient doping of high-valence ions through microwave heating, resulting in a more stable crystal structure. Furthermore, microwave heating yields a uniform, complete, and dense carbon coating layer, causing the byproducts after LFO detachment to remain inert, preventing side reactions that consume active lithium, thereby reducing capacity loss during cycling and extending cycle life.

[0087] In some specific embodiments, the lithium-ion battery containing the modified LFO lithium replenishing agent material has a gas production rate of ≤0.6 mL / Ah after storage at 55°C for 60 days. The modified LFO lithium replenishing agent material provided by the present invention has a low residual alkali content and a more stable crystal lattice after high-valence ion doping. The by-products after delithiation do not break down, avoiding the formation of new interfaces, thus effectively suppressing gas production during high-temperature storage cycling of the battery made from it.

[0088] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0089] Example 1 The preparation method of the modified LFO lithium supplement material provided in this embodiment includes the following steps: (1) Weigh lithium carbonate, iron nitrate, cerium nitrate and ammonium metavanadate according to the molar ratio of Li, Fe, Ce and V as 5:0.99:0.005:0.005 (i.e., doping amount: Ce 5000ppm, V 5000ppm, where ppm is molar fraction), and dissolve them all in water. Then add citric acid complexing agent and mix thoroughly. The molar amount of complexing agent is 1.5 times the molar amount of Fe in iron nitrate. After complete dissolution, a mixed system is obtained. The mixed system is heated and evaporated in a water bath at 80℃ for 6h, and then dried to form a dry gel.

[0090] (2) The above-mentioned dry gel was placed in a tube furnace and high-purity nitrogen was introduced. It was heated at 320°C for 3 hours for pre-decomposition. After cooling, a powdered precursor material was obtained.

[0091] (3) The above precursor material is loaded into a corundum container and then placed in the microwave reaction cavity of the microwave energy micro-area targeted heater. High-purity nitrogen is introduced to prevent ferrous iron from being oxidized to ferric iron. Then, intermittent microwave heating is performed: first heat for 5 minutes, then let stand for 5 minutes, and repeat this process 4 times, for a total of 20 minutes of heating. The power is set to 600W to obtain powdered crystal material.

[0092] (4) After mixing glucose, polyethylene glycol and water evenly to obtain a carbon source solution, the above-mentioned crystal material is added to it and ground and mixed evenly. The mass ratio of glucose, polyethylene glycol and crystal material is 3:1.5:95.5. Then, it is dried at 90°C and then subjected to intermittent low-temperature microwave treatment: first heat for 5 minutes, then let stand for 5 minutes, repeat this process 3 times, that is, heat for a total of 15 minutes, and set the power to 300W to obtain the modified LFO lithium supplement material.

[0093] The modified LFO lithium replenisher material has a particle size D50 of 8 μm. It comprises a lithium replenisher matrix and a carbon coating layer covering the matrix. The chemical formula of the lithium replenisher matrix is ​​Li5Fe. 0.99 Ce 0.005 V 0.005 O4, the carbon coating thickness is 5nm, and the carbon content in the modified LFO lithium supplement material is 1.8wt.%.

[0094] Example 2 The preparation method of the modified LFO lithium supplement material provided in this embodiment differs from that in Example 1 in that: in step (1), the molar ratio of Li, Fe, Ce and V is replaced with 5:0.998:0.001:0.001 (i.e., doping amount: Ce 1000ppm, V 1000ppm, where ppm is the molar fraction).

[0095] The chemical formula of the lithium supplement matrix obtained in this embodiment is Li5Fe. 0.998 Ce 0.001 V 0.001 O4.

[0096] Example 3 The difference between the preparation method of the modified LFO lithium supplement material provided in this embodiment and that in Example 1 is that in step (1), the molar amount of the complexing agent is 1.2 times the molar amount of Fe element in ferric nitrate.

[0097] Example 4 The difference between the preparation method of the modified LFO lithium supplement material provided in this embodiment and that in embodiment 1 is that: in step (3), the parameters of the intermittent microwave heating are as follows: first heat for 5 minutes, then let stand for 5 minutes, repeat this process 3 times, that is, heat for a total of 15 minutes, and the power is 800W.

[0098] Example 5 The difference between the preparation method of the modified LFO lithium supplement material provided in this embodiment and that in embodiment 1 is that: in step (4), the parameters of the intermittent low-temperature microwave treatment are as follows: first heat for 5 minutes, then let stand for 5 minutes, repeat this process 4 times, that is, heat for a total of 20 minutes, and the power is 200W.

[0099] Example 6 The preparation method of the modified LFO lithium supplement material provided in this embodiment differs from that in Example 1 in that: in step (1), lithium carbonate, iron nitrate, titanium tetrachloride and niobium oxalate are weighed according to the molar ratio of Li, Fe, Ti and Nb elements as 5:0.994:0.003:0.003 (i.e., doping amount: Ti 3000ppm, Nb 3000ppm, where ppm is molar fraction).

[0100] The chemical formula of the lithium supplement matrix obtained in this embodiment is Li5Fe. 0.994 Ti 0.003 Nb 0.003 O4.

[0101] Example 7 The difference between the preparation method of the modified LFO lithium supplement material provided in this embodiment and that in Example 1 is that in step (1), lithium carbonate, iron nitrate, ammonium molybdate and praseodymium nitrate are weighed according to the molar ratio of Li, Fe, Mo and Pr elements of 5:0.98:0.01:0.01 (i.e., doping amount: Mo 10000ppm, Pr 10000ppm, where ppm is the molar fraction).

[0102] The chemical formula of the lithium supplement matrix obtained in this embodiment is Li5Fe. 0.98Mo 0.01 Pr 0.01 O4.

[0103] Comparative Example 1 LFO as a lithium supplement material was synthesized using a traditional solid-state method, specifically including the following steps: Lithium carbonate and ferric oxide were weighed according to a Li to Fe molar ratio of 5:1, and then glucose and polyethylene glycol of the same mass as in Example 1 were weighed; all substances were ground and mixed evenly, and then sintered at 750°C for 10 hours under a N2 atmosphere to obtain a solid-state LFO lithium supplement material with a carbon content of 2 wt.%.

[0104] Comparative Example 2 The preparation method of the LFO lithium supplement material provided in this comparative example differs from that in Example 1 in that: in step (1), lithium carbonate and iron nitrate are weighed according to the molar ratio of Li to Fe of 5:1, that is, no M source is added, and undoped LFO is prepared; and step (4) is different. Step (4) of this comparative example is solid-phase coating. The specific method is as follows: weigh glucose and polyethylene glycol of the same mass as in Example 1, grind and mix the above undoped LFO with glucose and polyethylene glycol evenly, and sinter at 750°C for 5 hours under N2 atmosphere to obtain LFO lithium supplement material with carbon content of 2wt.%.

[0105] Comparative Example 3 The difference between the preparation method of the LFO lithium supplement material provided in this comparative example and that in Example 1 is that: in step (3), intermittent microwave heating was not performed, but the material was placed in a muffle furnace and sintered at 750°C for 12 hours under N2 atmosphere.

[0106] Comparative Example 4 The difference between the preparation method of the LFO lithium supplement material provided in this comparative example and that in Example 1 is that: in step (4), intermittent low-temperature microwave treatment was not performed, but the material was placed in a muffle furnace and sintered at 500°C for 5 hours under N2 atmosphere.

[0107] Experimental Example The residual alkali content of the modified LFO lithium supplement materials prepared in each embodiment and the LFO lithium supplement materials prepared in each comparative example (collectively referred to as the test materials) was determined by the following test methods: (1) Sample preparation: ① Aqueous System: Weigh 0.3g of the test material into a clean, dry 100mL gas washing bottle, then add 100mL of purified water to the gas washing bottle. Stir at 800rpm for 5 minutes (using a 3cm magnetic stir bar). After stirring, vacuum filter using a 50mm diameter, 0.2µm pore size aqueous microporous filter membrane. Collect the filtrate in a 100mL volumetric flask. Prepare two parallel samples. Ensure that all utensils and equipment that come into contact with the test material are thoroughly cleaned with purified water.

[0108] ② Organic system: Weigh 0.3g of the test material into a 100mL clean and dry gas washing bottle, then add 100mL of methanol to the gas washing bottle and stir at 800rpm for 5 minutes (using a 3cm magnetic stir bar). After stirring, vacuum filter the solution using a 50mm diameter, 0.2pm organic microporous filter membrane. Collect the filtrate into a 100mL volumetric flask and prepare two parallel samples. Ensure that all utensils and equipment that come into contact with the test material are thoroughly cleaned with pure water.

[0109] (2) Tests: Aqueous system: 2 ml of aqueous filtrate was added to a titration cup and diluted with pure water to 40 ml; Organic system: 40 ml of organic filtrate was added to a titration cup; titration was performed with 0.01 M HCl standard solution to obtain a titration curve. The lithium carbonate content was calculated based on the amount of hydrochloric acid used in the aqueous system method, and the lithium hydroxide content was calculated based on the amount of hydrochloric acid used in the organic system method. The residual alkali content was the sum of the lithium hydroxide and lithium carbonate contents. The test results are shown in Table 1 below, where the unit of residual alkali content ppm is the mass fraction.

[0110] Furthermore, the modified LFO lithium replenishing agent materials prepared in each embodiment and the LFO lithium replenishing agent materials prepared in each comparative example were respectively prepared into 4Ah soft-pack batteries under the same conditions. The battery preparation method is as follows: the positive electrode main material LFP, lithium replenishing agent material, SP, CNT and PVDF were mixed in a solvent at a mass ratio of 94%:2%:1%:1%:2% and homogenized. The viscosity of the discharged material was controlled at 6000mPa·s. The positive electrode slurry was coated on carbon-coated aluminum foil with an areal density of 20mg / cm³. 2 After roller pressing, the compacted weight is 2.4 g / cm³. 3 The negative electrode material is artificial graphite, with a charging capacity of 380 mAh / g. Graphite, SP, CMC, and SBR are mixed in a solvent at a mass ratio of 96%:1%:1.3%:1.7% to obtain a negative electrode slurry, which is then coated onto a 6 μm thick copper foil, resulting in an areal density of 9.59 mg / cm³. 2 The charging N / P ratio is 1.06, and the compaction weight after roller pressing is 1.5 g / cm³. 3 Then, the components are assembled, and the diaphragm is an Enjie 9+1+1 diaphragm. The electrolyte composition by mass percentage is: LiFP6 13%, EC 30%, EMC 23.5%, DMC 30%, VC 3%, and DTD 0.5%.

[0111] Each of the pouch cells prepared above was subjected to charge capacity testing after formation, with the formation voltage range being 2.0~4.2V and the rate being 0.5C.

[0112] The high-temperature cycling performance and gas production tests of the prepared pouch batteries were conducted separately: At 45℃, the batteries were first charged to 3.65V with a constant current of 1C, then charged to the cutoff current of 0.05C with a constant voltage of 3.65V, and finally discharged to 2.0V with a constant current of 1C. This constitutes one charge-discharge cycle, and the discharge capacity of this cycle is the discharge capacity of the first cycle. The batteries were subjected to cyclic charge-discharge tests in the above manner, and the discharge capacity of the 1000th cycle was recorded. The capacity retention rate (%) of the battery after 1000 cycles at 45℃ is calculated as (discharge capacity of the 1000th cycle / discharge capacity of the first cycle) × 100%. The gas production was calculated by subtracting the battery volume before and after 1000 cycles using the water displacement method.

[0113] The gas production of each of the prepared soft-pack batteries was then tested at 55°C for 60 days: At 25°C, the battery was charged at a constant current of 0.33C to a voltage of 3.65V, then charged at a constant voltage of 3.65V until the current ≤0.05C, and then discharged at a constant current of 0.33C to a voltage of 2V. The actual discharge capacity of the battery was recorded as C0. At 25°C, the battery was continued to be charged at a constant current of 0.33C0 to a voltage of 3.65V, then charged at a constant voltage of 3.65V until the current ≤0.05C0. At this point, the battery was fully charged, and the volume of the battery was measured and recorded as the volume before storage. The fully charged battery was placed in a constant temperature chamber at 55°C for 60 days. After storage, the battery was removed from the constant temperature chamber and its volume was measured and recorded as the volume after 60 days of storage. The gas production of the battery after 60 days of storage at 55°C (mL / Ah) = (Volume after 60 days of storage - Volume before storage) / Rated capacity of the battery.

[0114] The test results for each electrical performance are shown in Table 1 below.

[0115] Table 1 Summary of Test Results

[0116] As shown in Table 1, compared with Comparative Example 3, the residual alkali content in the LFO lithium supplement material prepared by microwave heating in Example 1 is significantly lower, only 1 / 3 of that in Comparative Example 3.

[0117] Furthermore, the specific capacity of the modified LFO lithium replenishing agent materials obtained in each embodiment is significantly improved compared with the comparative example. It can be seen that the solution provided by the present invention has a significant optimization effect in terms of capacity improvement. This is because: the material prepared by microwave heating method achieves efficient doping of high valence ions, which widens the lithium ion transport channel and thus improves the lithium ion diffusion rate and increases the specific capacity of the material; and this method obtains a complete conductive network by carbon coating, thereby further promoting its capacity performance.

[0118] From the perspectives of capacity retention, gas production, and high-temperature storage gas production after 1000 cycles at 1C / 1C, compared to the comparative example, the capacity retention of each embodiment is significantly improved, and the gas production during high-temperature cycling and storage is significantly reduced. It can be seen that the modified LFO lithium replenishing agent material provided by the present invention has improved cycling performance and reduced gas production at high temperatures. This is because the microwave heating method enables efficient doping of high-valence ions in the material, making the material's crystal structure more stable. Furthermore, the carbon coating layer formed by the microwave heating method is more uniform, complete, and dense, so that the byproducts after LFO detachment are in an inert state, and no side reactions consume active lithium. This reduces capacity loss during cycling and extends cycle life. It also prevents the oxidation of the electrolyte during high-temperature cycling and storage, thus reducing continuous gas production and lowering the gas production. In summary, the modified LFO lithium supplement material provided by this invention has advantages such as high capacity, excellent cycle performance, and low gas production during high-temperature cycle storage. It also exhibits excellent comprehensive electrochemical performance. Furthermore, the modified LFO lithium supplement material has a low residual alkali content, which can suppress side reactions with the binder during the slurry preparation process, ensuring stable viscosity of the lithium supplement slurry and thus improving processing performance.

[0119] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.

Claims

1. A modified LFO lithium supplement material, characterized in that, It includes a lithium replenishing agent matrix and a carbon coating layer covering the lithium replenishing agent matrix; The general formula of the lithium supplement matrix is ​​Li5Fe 1-x M x O4; where M is a high-valence dopant ion, and the valence of the high-valence dopant ion is +4, +5 or +6; and 0.001≤x≤0.02; The residual alkali content in the modified LFO lithium supplement material is ≤1000ppm.

2. The modified LFO lithium supplement material according to claim 1, characterized in that, The high-valence doped ions include V 5+ 、Nb 5+ Mo 6+ Ti 4+ Ce 4+ and Pr 4+ One or more of the following; Preferably, 0.01 < x ≤ 0.

02.

3. The modified LFO lithium supplement material according to claim 1, characterized in that, The thickness of the carbon coating layer is 2nm~10nm; And / or, the carbon content in the modified LFO lithium supplement material is 1 wt.% to 3 wt.%.

4. The modified LFO lithium supplement material according to claim 1, characterized in that, The particle size D50 of the modified LFO lithium supplement material is 2μm~12μm.

5. The method for preparing the modified LFO lithium supplement material according to any one of claims 1 to 4, characterized in that, Includes the following steps: Precursor materials are prepared by mixing lithium source, iron source, M source and solvent; The precursor material is subjected to intermittent microwave heating, which causes the high-valence doped ions M in the M source to enter the LFO lattice, thereby obtaining a crystal material. The crystalline material is mixed with a carbon source solution and dried, then microwaved to form a carbon coating layer, thus obtaining a modified LFO lithium supplement material.

6. The preparation method of the modified LFO lithium supplement material according to claim 5, characterized in that, The intermittent microwave heating includes alternating heating and resting phases, with the number of cycles being 2 to 6. The duration of each heating phase is 2.5 to 5 minutes, the duration of each resting phase is 2.5 to 5 minutes, the total duration of each heating phase is 5 to 30 minutes, and the power is 400W to 800W. Preferably, the container holding the precursor material for intermittent microwave heating is a quartz container or a corundum container.

7. The preparation method of the modified LFO lithium supplement material according to claim 5, characterized in that, The method for preparing precursor materials by mixing lithium source, iron source, M source and solvent specifically includes: The lithium source, iron source, M source, solvent and complexing agent are mixed, heated and evaporated and then dried to obtain a dry gel; The dry gel is pre-decomposed by heating to obtain the precursor material; Preferably, the heating and evaporation is carried out by water bath heating, the heating and evaporation temperature is 70℃~90℃, and the heating and evaporation time is 5h~10h; Preferably, the solvent includes water; Preferably, the complexing agent comprises at least one of citric acid and EDTA; Preferably, the molar amount of the complexing agent is 1.2 to 2.0 times the molar amount of Fe in the iron source; Preferably, the heating pre-decomposition temperature is 300℃~350℃, the heating pre-decomposition time is 2h~4h, and the heating pre-decomposition atmosphere is an inert atmosphere.

8. The preparation method of the modified LFO lithium supplement material according to claim 5, characterized in that, At least one of the following conditions must be met: (1) The carbon source in the carbon source solution includes at least one of sucrose, glucose and polyethylene glycol; (2) In the process of drying the crystal material after mixing it with the carbon source solution, the drying temperature is 80℃~100℃; (3) The microwave treatment method for forming the carbon coating layer is an intermittent low-temperature microwave treatment, specifically including alternating heating treatment and static treatment. The number of cycles is 2 to 4, the time of each heating treatment is 2.5 min to 5 min, the time of each static treatment is 2.5 min to 5 min, the total time of each heating treatment is 5 min to 20 min, and the power is 200 W to 400 W.

9. A positive electrode plate, characterized in that, It includes a positive current collector and a positive electrode material layer disposed on the surface of the positive current collector; the positive electrode material layer contains a modified LFO lithium supplement material as described in any one of claims 1 to 4 or a modified LFO lithium supplement material prepared by the preparation method of the modified LFO lithium supplement material according to any one of claims 5 to 8.

10. A lithium-ion battery, characterized in that, Includes the positive electrode as described in claim 9; Preferably, the lithium-ion battery satisfies at least one of the following conditions: (1) The 0.5C charging capacity of the lithium-ion battery is ≥750mAh / g; (2) The lithium-ion battery, at 45°C and 2.0~3.65V, produces ≤0.5mL / Ah gas per 1000 cycles at 1C / 1C. (3) The gas production of the lithium-ion battery stored at 55°C for 60 days is ≤0.6mL / Ah; (4) The lithium-ion battery retains ≥97% of its capacity at 45°C and 2.0~3.65V voltage for 1000 cycles at 1C / 1C.